Development of Student Activity Sheets (LAPD) Oriented to Project Based Learning (PjBL) to Improve Chemical Literacy Skills on Redox Material - Suryawan, Karina Ristya; Mitarlis, Mitarlis (Universitas Pendidikan Mandalika, 2024)
In the era of 21st century skills, the literacy scores of Indonesian students according to the results of the PISA study (2022) are still relatively low. The existence of learning loss after the covid-19 pandemic has had an impact on reducing learning outcomes and students' chemical literacy skills on redox material. This research aims to produce LAPD oriented to project based learning to improve chemical literacy skills on redox material. The method used is Research and Development (R&D) with a 4D model (define, design, develop, disseminate), but is limited to the develop stage. In this research, a limited trial was conducted on 29 students in 11th Grde Science 2 class, at a private school in Mojokerto, who had received redox material. Data analysis was carried out descriptively quantitatively. The validity (content and construct) of LAPD is valid, obtaining a mode of 4 with a good category. The practicality of LAPD is practical, the results of the student response questionnaire obtained a percentage of 96.78% with a very good category. The effectiveness of LAPD iseffective, the n-gain of the chemical literacy test with a high category of 93.10% and a medium category of 6.90%; and the results of the paired sample t-test obtained a Sig.2-tailed value of 0.000 < 0.05 so that H0 is rejected and H1 is accepted. Thus, it can be concluded that LAPD oriented to project based learning to improve chemical literacy skills on redox material, worthy of use